Structure and Function of Oral Literature in the Datu Kuning Folklore of Bulungan - Ariny Andany; Hicham Kasmi; Jahnese Asuncion (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to describe the narrative structure and the oral literature functions found in the Datu Kuning folktale of Tanah Kuning Village by applying a structural approach to identify its plot, characters, setting, theme, and cultural functions. Methodology: This research uses a qualitative descriptive method supported by observation, interviews, audio-recording techniques, note-taking, and documentation. The researcher functions as the main instrument, collecting data from community informants who possess knowledge of the Datu Kuning folktale. Data were analyzed through collection, reduction, display, and conclusion procedures. Main Findings: The study identifies a forward-moving plot; main characters consisting of Datu Kuning and Datu Mahkota; and additional character Datu Badaruddin. The setting includes 20 place settings, 12 time settings, and 8 socio-cultural settings. The theme centres on a royal kingdom. The folktale also contains four educational functions, three cultural preservation functions, three motivational functions, and two recreational functions, resulting in 57 total data items. Novelty/Originality of this study: This study provides the first structural analysis of the Datu Kuning folktale, documenting its narrative elements and functional roles comprehensively. It contributes new knowledge by preserving an overlooked oral tradition, offering systematic categorization of its cultural values, and supporting future research on local folklore and oral literature preservation.